Um modelo SIR com duas cepas circulantes - Oliveira, Maiquel Juliano Rodrigues de (2023)
To understand the evolution of many diseases such as influenza and COVID-19, for example, it is necessary to consider the presence of multiple strains of the pathogen. Models with multiple strains of the disease-causing agent can be used to identify the dominant strains and thus design more efficient control strategies. In this work, using the SIR model with vital dynamics, we study the dynamics of a disease in which there are two strains of the pathogen. As in ecological models, the strains compete for a common resource, in this case, susceptibles. We show that when there is complete cross-immunity, the strain with the highest basic reproductive number will be the dominant strain. The coexistence of the two strains is impossible in this case. We then present a model that indirectly considers the mutation of the pathogen. A fraction of the infected by strain 1 is transferred to the class of those infected by strain 2. We conclude that this mechanism makes it possible for the two strains to coexist.